Early signs of multi-walled carbon nanotbues degradation in macrophages, via an intracellular pH-dependent biological mechanism; importance of length and functionalization. Issue 1 (December 2016) - Landry, Marion; Pinault, Mathieu; Tchankouo, Stéphane; Charon, Émeline; Ridoux, Audrey; Boczkowski, Jorge; Mayne-L'Hermite, Martine; Lanone, Sophie
Abstract Background Carbon nanotubes (CNT) can interact with the biological environment, which could participate in their associated toxicity. We recently demonstrated that pH is an important player of CNT fate inside macrophages. We wanted to further characterize such process, and therefore designed a study dedicated to decipher CNT biodegradation by macrophages, as a function of two major physico-chemical properties in regard with nanotoxicology; length and degree of functionalization. To achieve our aim, we synthesized, following a single initial production process, four MWCNT differing in length and/or surface chemistry: S-CNT (short), SF-CNT (short functionalized), L-CNT (long) and LF-CNT (long functionalized). Results Raman spectroscopy analysis performed on CNT recovered after exposure of RAW 264.7 macrophages for 6, 24, or 48 h demonstrate that CNT show early signs of biodegradation over time inside macrophages. The modulation of CNT length and functionalization, resulting in the modification of iron accessibility, both represent critical determinants of the biodegradation process; short pristine CNT were more prone to biodegradation than long CNT (pristine or functionalized), while short functionalized CNT were protected. Incubation of cells with Concanamycin completely prevents CNT from being modified, demonstrating that this biodegradation process is dependent on an intracellular pH-dependent mechanism. Interestingly, and despite evidence of degradation via Raman spectroscopy, the CNT length and diameter were not altered during the course of the study. Conclusions In conclusion, our results identify a new mechanism of CNT biodegradation inside macrophages. This could give new insights for the understanding of CNT-associated toxicity, and represent important tools to develop safe(r)-by-design nanomaterials.